Circumvention of common labelling artefacts using secondary nanobodies. Issue 18 (1st May 2020) - Sograte-Idrissi, Shama; Schlichthaerle, Thomas; Duque-Afonso, Carlos J.; Alevra, Mihai; Strauss, Sebastian; Moser, Tobias; Jungmann, Ralf; Rizzoli, Silvio O.; Opazo, Felipe
Abstract : Secondary nanobodies can minimize probe-induced clusters artefacts. Their small size also allows fast sample penetration, and their monovalent binding enables multiplex staining using primaries from the same species. Abstract : A standard procedure to study cellular elements is via immunostaining followed by optical imaging. This methodology typically requires target-specific primary antibodies (1.Abs), which are revealed by secondary antibodies (2.Abs). Unfortunately, the antibody bivalency, polyclonality, and large size can result in a series of artifacts. Alternatively, small, monovalent probes, such as single-domain antibodies (nanobodies) have been suggested to minimize these limitations. The discovery and validation of nanobodies against specific targets are challenging, thus only a minimal amount of them are currently available. Here, we used STED, DNA-PAINT, and light-sheet microscopy, to demonstrate that secondary nanobodies (1) increase localization accuracy compared to 2.Abs; (2) allow direct pre-mixing with 1.Abs before staining, reducing experimental time, and enabling the use of multiple 1.Abs from the same species; (3) penetrate thick tissues more efficiently; and (4) avoid probe-induced clustering of target molecules observed with conventional 2.Abs in living or poorly fixed samples. Altogether, we show how secondary nanobodies are a valuable alternative to 2.Abs.